Composition dependent polymorphism and superconductivity in Y3+x{Rh, Ir}4Ge13−x. Issue 12 (4th March 2022) - Feig, Manuel; Carrillo-Cabrera, Wilder; Bobnar, Matej; Simon, Paul; Curfs, Caroline; Levytskyi, Volodymyr; Tsirlin, Alexander A.; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : Polymorphism is observed in the Y3+ x Rh4 Ge13− x  series of superconductors. Abstract : Polymorphism is observed in the Y3+ x Rh4 Ge13− x series. The decrease of Y-content leads to the transformation of the primitive cubic Y3.6 Rh4 Ge12.4 [ x = 0.6, space group Pm 3̄ n, a = 8.96095(9) Å], revealing a strongly disordered structure of the Yb3 Rh4 Sn13 Remeika prototype, into a body-centred cubic structure [La3 Rh4 Sn13 structure type, space group I 41 32, a = 17.90876(6) Å] for x = 0.4 and further into a tetragonal arrangement (Lu3 Ir4 Ge13 structure type, space group I 41 / amd, a = 17.86453(4) Å, a = 17.91076(6) Å) for the stoichiometric ( i.e. x = 0) Y3 Rh4 Ge13 . Analogous symmetry lowering is found within the Y3+ x Ir4 Ge13− x series, where the compound with Y-content x = 0.6 is crystallizing with La3 Rh4 Sn13 structure type [ a = 17.90833(8) Å] and the stoichiometric Y3 Ir4 Ge13 is isostructural with the Rh-analogue [ a = 17.89411(9) Å, a = 17.9353(1) Å]. The structural relationships of these derivatives of the Remeika prototype are discussed. Compounds from the Y3+ x Rh4 Ge13− x series are found to be weakly-coupled BCS-like superconductors with T c = 1.25, 0.43 and 0.6, for x = 0.6, 0.4 and 0, respectively. They also reveal low thermal conductivity (<1.5 W K −1 m −1 in the temperature range 1.8–350 K) and small Seebeck coefficients. The latter are common for metallic systems. Y3 Rh4 Ge13 undergoes a first-order phase transition at T f = 177 K, with signatures compatible to a charge density wave scenario. The electronic structure calculations confirm the instability of the idealized Yb3 Rh4 Sn13 -like structural arrangements for Y3 Rh4 Ge13 and Y3 Ir4 Ge13 .